Self Assessment Personal Social of Teacher Professional Participants in Post-SM3T Geography in the Field Experience Program - Nadya Hani (Universitas Nahdlatul Ulama Lampung, 2019)
Assessment in the Field Experience Program (PPL) shows the ability of Education participants Teacher profession (PPG) in teaching and describing the results of training for 1 semester of the workshop/workshop. One form of assessment that can be used is to use techniques Self Assessment that make the individual himself who assesses his abilities. Self Assessment as a way to act reflective in an effort to reach professional teachers. The purpose of this study is to provide an overview of social and personal competence from the perspective of PPG participants themselves when implementing PPL. The subjects of this study were PPG Post-Geography SMGT participants who had finished implementing PPL. The research method is survey. The results showed that the majority of PPG participants could implement or apply sub-indicators in personal social competencies with a minimal good enough category (scale 4). But there are still participants who find it difficult to sub-indicators that raise academic integrity, one of which is the topic of plagiarism.